PENGARUH MOTIVASI KERJA DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PT. KOSAMI SEJAHTERA UTAMA UNIT TERMINAL INSPECTION-T1, BANDAR UDARA SOEKARNO-HATTA TANGERANG - Noviyanti Noviyanti; Lia Asmalah; Juwita Ramadani Fitria (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the effect of work motivation and teamwork on employee performance. The research method used is a quantitative method with an associative approach. The population and sample in this study were employees of PT. Kosami Sejahtera Utama Terminal Inspection unit- T1. Test Instruments used are Validity Test and Reliability Test. Classical assumption tests, Quantitative Analysis include Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Correlation Coefficient and Determination Coefficient. Test the Hypothesis used. The results of this study show that work motivation partially has a significant effect on employee performance with a calculated t value greater than the table t (6.187 > 2.001). Teamwork partially has a significant effect on employee performance with t values calculated at 4.872 > 2.001. Simultaneously, the results of data processing show that work motivation and teamwork have a positive and significant effect on the performance of PT. Kosami Sejahtera Utama Terminal Inspection-T1 unit with a calculated F value of 23.516 and a coefficient of determination value of 44.8% while the remaining 55.2% is influenced by other factors. The conclusion of this study is that there is a positive and significant influence between work motivation with employee performance and teamwork with employee performance